Court location does not affect female collegiate basketball players' shooting movement pattern - Leigh, S.; Pearson, T.; Chhabra, J.; Konz, S. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The core basketball shooting movement pattern includes a coordinated sequence of a countermovement followed by shoulder flexion then elbow extension, parameterized by distance to the basket. We assessed how this core shooting movement pattern varied among different court locations. Two cameras recorded videos of a collegiate women`s basketball team (n = 11) shooting from four court locations. 3-D whole-body kinematics were measured by identifying joint centres in the videos, direct linear transformation of 2-D video coordinates, and Euler angle calculations. A principal component analysis was run and identified four relative timing components of the core basketball shooting movement pattern, which did not vary with court location (Lambda1 = 3.94, Lambda2 = 3.33, Lambda3 = 1.55, Lambda4 = 1.00). Basketball shooting technique is more complex than commonly coached, but robust.